PENGEMBANGAN ALAT EVALUASI MENGGUNAKAN MEDIA QUIZIZZ BERBASIS PAPERMODE DI SDN TUNDAGAN - Magistra, Igra Tanjil; Nunu Nurfirdaus; Nana Sutarna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was intended to make an evaluation tool using Quizizz based on Papermode to improve the motivation and learning outcomes of fourth-grade students in IPAS at SDN Tundagan. The issues addressed include the limited variety of evaluation methods and student engagement in learning, with the expectation of providing an effective solution. This study employs the Research and Development (R&D) methodology with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data were gathered from interviews, questionnaires, and observations of students and teachers. Validation was conducted by experts in media, content, and technology to ensure the suitability and effectively of the evaluation tool that was developed. The findings showed that the evaluation tool using the Quizizz-based Papermode media was deemed highly suitable, with a validation percentage of 96.67% by media experts, 94.00% by technology experts, and 92.00% by content experts. Students gave a positive response with a score of 91.63%, indicating an enhancement in motivation and engagement in IPAS learning in the fourth grade at SDN Tundagan. By this research, it is identified that the Quizizz-based Papermode evaluation tool effectively enhances student motivation and learning outcomes in the fourth grade for the IPAS subject. It is recommended that teachers utilize this media regularly and incorporate visual elements to capture students' attention, as well as provide training to optimize the use of technology in learning.